Obstructive Ileus Secondary to Acute Mesenteric Ischaemia: Internal Medicine Perspective - M Rosyid Narendra; Herry Purbayu (The Indonesian Society for Digestive Endoscopy, 2021)
Acute mesenteric ischemia (AMI) could be a rare but potentially life-threatening condition due to poor understanding of the clinical presentation of abdominal pain and the differential diagnosis when it is not suspected and partly because of an unacceptable delay in making the diagnosis. A 59 years old man was brought to the hospital with abdominal pain, accompanied by obstructive ileus and sepsis. An urgent CT-scan showed the feature of intestinal infarction and portal vein thrombus. After giving fluid resuscitation and antibiotic injection, he was consulted to the surgery division and had jejunum resection. Since the etiology of the disease was suspected to be acute mesenteric venous thrombosis, he was given intravenous anticoagulants postoperatively and the condition improved. The clinical diagnosis of acute mesenteric ischemia is troublesome, and in most cases, abdominal pain is the main symptom. Ileus and sepsis are two complications that may mask the initial signs and symptoms of AMI. From the internal medicine’s point of view, the proper treatment of this disease is early diagnosis, the rebuilding of blood flows with anticoagulants, surgery division discussion, and post-operative supportive care. The underlying cause should be established to determine long-term management essential to anticipate a repeat.